Comparison of trained panel and consumers’ methodologies to discriminate chocolate samples based on industry quality control parameters - CEMIN, Paloma; MORAES, Bruna Klein Borges de; SANT’ANNA, Voltaire (Food Science and Technology, 2023)
The aim of this study was to compare sensory trained panel and consumers’ characterization of chocolates based on a factory’s quality control attributes. Six chocolates were evaluated by a trained panel using descriptive analysis and consumers using Check-All-That-Apply for chocolate, bitter, alkalinity, acidity, woody, smoked, green, floral, burned, musty, and cocoa flavors. Analysis of variance, multivariate analysis-based reduction of dimensions, and multiple factor analysis were performed. The results show that the trained panel and consumers discriminated chocolate samples differently. Trained accessors characterized chocolates made of cocoa liquor from Rondônia and Bahia and those from organic cocoa from Pará to present chocolate and floral flavors; samples from Pará, Espírito Santo, and Cotê d’Ivoire were associated with alkalinity, acidity, smoked, burnt, cocoa, musty, bitter, green, and astringent flavors. Consumers perceived chocolate made of cocoa from Pará to musty, woody, smoked, and alkalinity flavors; chocolate made of liquor from Espírito Santo to burned, green, and astringent flavors; samples made of cocoa from Bahia and Cotê d’Ivoire were associated with bitterness; and those chocolates with Rondônia and organic sample from Pará were associated with floral, cocoa, and chocolate flavors. Multiple factor analysis indicated that consumers perceived samples close to trained panel when chocolates presented wider attribute intensity profile.